Changes of ACE2 in different glucose metabolites and its relationship with COVID-19. Issue 41 (14th October 2022) - Lu, Yamin; Xing, Chenhao; Lv, Xiuqin; Zhang, Cuigai; Liu, Guangxia; Chen, Fang; Hou, Zhan; Zhang, Donghui
Abstract : Background: To study the changes and effects of angiotensin-converting enzyme 2 (ACE2)/angiotensin 1-7 (Ang1-7) and ACE/AngII in people with different glucose metabolisms and to explore the possible mechanisms underlying the severity of COVID-19 infection in diabetic patients. Methods: A total of 88 patients with type 2 diabetes, 72 patients with prediabetes (impaired fasting glucose, 30 patients; impaired glucose regulation, 42 patients), and 50 controls were selected. Changes and correlations of ACE2, Ang1-7 and other indicators were detected among the three groups. Patients were divided into four groups according to the course of diabetes: <1 year, 1–5 years, 5–10 years, and >10 years. ACE2 and Ang1-7 levels were compared and analyzed. Results: ACE2 and Ang1-7 increased with the severity of diabetes ( P 0 < .05 or P < .01). The levels of ACE2 and Ang1-7 in the longer course group were lower than those in the shorter course group, whereas the levels of ACE, Ang II, and interleukin-6 (IL-6) gradually increased ( P < .05). Pearson correlation analysis showed that ACE2 was positively correlated with IL-6, FBG, and 2hPBG levels in the prediabetes group. In the diabetic group, ACE2 was positively correlated with Ang1-7 and negatively correlated with ACE, AngII, IL-6, and C-reactive protein levels. Multiple linear regression analysis showed that IL-6 and ACE were the main factors influencing ACE2 in the diabetic group. Conclusion subsections: ACE2/Ang1-7 and ACE/AngII systems are activated, and inflammatory cytokine release increases in prediabetes. With the prolongation of the disease course, the effect of ACE2/Ang1-7 decreased gradually, while the effect of ACE/AngII increased significantly. Dysfunctions of ACE2/Ang1-7 may be one of the important mechanisms underlying the severity of COVID-19 infection in patients with diabetes.